PENGARUH PENEMPATAN (PLACEMENT) DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT UMUM DAERAH (RSUD) MADISING KABUPATEN PINRANG - Yusuf, Hakim Sugito (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
The new paradigm of health care requires hospitals to provide quality services according to the needs and desires of patients while still referring to the professional code of ethics. In the rapid development of technology and increasingly fierce competition, hospitals are required to continue to improve the quality of their services. The phenomenon behind this research by looking at the conditions of handling employee placements in hospitals is very different from handling employee placements in agencies/institutions in general, so the goal to be achieved in this study is to find out whether the pattern of placement and job satisfaction can improve performance. Employees at the Regional General Hospital (RSUD) Pinrang Regency. The results of this study are that the placement has no significant effect on the performance of the Pinrang Regency General Hospital (RSUD) and the results of other analyzes, namely job satisfaction, show a strong and significant influence and relationship.